Numerical analysis of limit states for circular concrete-filled steel tubular columns based on stiffness degradation. Issue 24 (12th December 2020) - Guan, Minsheng; Xiao, Qian; Lin, Siying; Cui, Jie; Du, Hongbiao; Lai, Zhichao
Abstract : In this paper, the stiffness degradation index previously proposed by the authors is used as a seismic performance index for circular concrete-filled steel tubular (CFT) columns. Four performance levels for CFT columns are defined – that is, virtually intact; minor damage; moderate damage; and severe failure. A total of 144 CFT columns are numerically analysed to obtain the stiffness degradation index values for each performance level. The effects of several parameters (i.e. the axial compression ratio, slenderness ratio, diameter-to-thickness ratio, yield strength of a steel tube, and compressive strength of concrete cylinder) on the stiffness degradation index for each performance level are investigated. The results show that the axial compression ratio has a substantial effect on all performance levels; the diameter-to-thickness ratio has a significant effect on the virtually intact and minor damage performance levels; and the slenderness ratio has a significant effect on the moderate damage performance level. An equation that estimates the value of the performance level is proposed by the regression analysis and is further verified using existing experimental results. Based on parameter expansion analysis, the preliminary limit of the stiffness degradation index for each performance level is proposed.